2018
DOI: 10.1111/mmi.13924
|View full text |Cite
|
Sign up to set email alerts
|

What is Vipp1 good for?

Abstract: Summary While Vipp1 (also known as IM30) clearly is essential for proper biogenesis of thylakoid membranes in chloroplasts and cyanobacteria, the exact function of Vipp1/IM30 still remains unclear. The recent in vivo study of Gutu et al. now demonstrates that Vipp1/IM30 forms localized puncta specifically at highly curved membrane regions at the cell periphery. These Vipp1/IM30 puncta were found being highly dynamic under normal growth conditions, while it has recently been shown that they stably associate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Previously, it has been shown that IM30 forms carpet structures on negatively charged membrane surfaces that can stabilize membranes (19). This observation is in perfect agreement with a membrane protecting activity suggested before for IM30 and PspA family members, as well as with the formation of large membrane covering structures under (membrane) stress conditions observed in vivo (23,31). Yet, IM30 has also been shown to mediate membrane fusion, at least in vitro, which involves membrane destabilization.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previously, it has been shown that IM30 forms carpet structures on negatively charged membrane surfaces that can stabilize membranes (19). This observation is in perfect agreement with a membrane protecting activity suggested before for IM30 and PspA family members, as well as with the formation of large membrane covering structures under (membrane) stress conditions observed in vivo (23,31). Yet, IM30 has also been shown to mediate membrane fusion, at least in vitro, which involves membrane destabilization.…”
Section: Discussionsupporting
confidence: 92%
“…These carpets stabilize damaged membranes and thereby likely preserve the barrier function of the TMs (19). The in vitro observations explain the in vivo observed formation of large IM30 assemblies at defined TM regions in response to membrane stress conditions (23,31). Yet, while the membrane protecting activity of IM30 has been observed, IM30 triggers membrane fusion when Mg 2+ is present (10).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The inner membrane-associated protein of 30 kDa (IM30), also known as vesicle inducing protein in plastids (VIPP1), is a protein conserved in chloroplasts and cyanobacteria, where it is involved in thylakoid membrane (TM) biogenesis and/or maintenance [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . A striking feature of IM30 protein family members is the ability to form large homo-oligomeric super-complexes with masses exceeding 1 MDa [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…While diverse functions have been attributed to IM30 in the past 1,2,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] , most observations clearly indicate that the protein is membrane-active and involved in the biogenesis, dynamics and/or stabilization of internal membranes in chloroplasts and cyanobacteria (recently reviewed in 25 ). Thus, the physiological function of IM30 appears to be linked to dynamic membrane remodeling [25][26][27] , likely involving membrane fusion/fission events, which have been observed in plant chloroplasts [28][29][30][31] . In fact, dynamic rearrangement of the TM system is crucial for adaptation of photosynthetic processes to altering environmental conditions, most importantly in response to altering light intensities 32,33 .…”
mentioning
confidence: 98%